Endophyteinfected Festuca pratensis containing loline alkaloids deters feeding by Listronotus bonariensis - Patchett, B.J.; Chapman, R.B.; Fletcher, L.R.; Gooneratne, S.R. (New Zealand Plant Protection, 2008)
Meadow fescue Festuca pratensis infected with Neotyphodium uncinatum contains loline alkaloids that may deter attack from pasture insects In a field experiment conducted in Canterbury high leaf loline alkaloid concentration reduced damage by Argentine stem weevil (ASW; Listronotus bonariensis) adults to 12 unique endophyteinfected meadow fescue ecotypes at four assessment times (DecApr; R2adj 489 P